„Egyre jobban érdekel, hogy mi történik velem”: A hála pszichológiai jelentősége időskorban - FERENCZI, Andrea; RÓZSA, Sándor (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2025)
“I Am Increasingly Interested in What Is Happening to Me”: The Psychological Significance of Gratitude in Old Age. THEORETICAL BACKGROUND – According to the Hungarian Central Statistical Office (2024), individuals aged 65 and over represent 20.7% of the population, with an ageing index of 143.2%. As productivity declines and life approaches its closure, older adults often engage in life review, reflecting on their achievements and goals. This stage of life, however, also brings unique challenges and crises. Consequently, studies focusing on the preservation and enhancement of mental health in older age play a crucial role in psychology. GOALS – The present study aimed to examine the associations between dispositional gratitude and several psychological constructs of particular relevance in old age, including time perspective, perceived social support, hopelessness, psychological well-being, and religiosity. Furthermore, we investigated the potential effects of a gratitude intervention on these constructs among older adults. METHODS – A total of 161 participants aged 65 and above took part in the study, of whom 94 maintained a gratitude diary for four weeks. The experimental group (n = 94) was administered the questionnaires before and after the intervention, whereas the control group (n = 67) completed them at two corresponding time points. The test battery, delivered both online and in paper-and-pencil form, included the Gratitude Questionnaire (GRAT), the Zimbardo Time Perspective Inventory, the Social Support Questionnaire, the Beck Hopelessness Scale, and Ryff’s Psychological Well-Being Scale. Additional measures assessed religious practice and the subjective importance of faith. RESULTS – Analyses of the total sample confirmed that gratitude was positively associated with a past-positive time perspective and negatively correlated with both past-negative and present-fatalistic orientations. A strong negative correlation emerged between dispositional gratitude and hopelessness (r = –.50, p < .01), indicating that gratitude – by fostering the recognition and appreciation of positive experiences – functions as a protective factor against pessimistic attitudes and negative expectations about the future. Furthermore, dispositional gratitude showed a strong positive correlation with psychological well-being (r = .56, p < .01), indicating that higher levels of gratitude are associated with greater self-acceptance, stronger and more supportive social relationships, a clearer sense of purpose in life, and enhanced opportunities for personal growth. The experimental group that engaged in gratitude journaling demonstrated changes primarily in the more conscious appreciation of everyday positive experiences and in the more favourable reinterpretation of past-negative events. Nevertheless, consistent with our expectations, no significant group-level effects were found when compared to the control group. CONCLUSIONS – The findings underscore that gratitude is not merely a pleasant emotional state but a key psychological resource for maintaining mental health and fostering self-realization in old age. Gratitude-based interventions may serve as an efficacious means of enhancing psychological well-being and constitute a central component of positive psychology approaches. While gratitude journaling has been shown in prior studies to be an effective intervention, our results suggest that its impact may strongly depend on the specific characteristics of the target group, the context of implementation, and the sensitivity of the measurement instruments. Overall, our results suggest that gratitude in old age primarily acts as a protective factor; thus, its incorporation into prevention programmes may be particularly justified.